The Structure of Tagalog - Lopez, Cecilio (The Archive, 2025)
The first of the three articles of Dr. Lopez in this issue is a short but comprehensive grammar of Tagalog. It is essentially a condensed and updated version of his A Manual of the Philippine National Language (1941).